A Comparative Cross-Sectional Study Assessing the Psycho-Emotional State of Intensive Care Units’ Physicians and Nurses of COVID-19 Hospitals of a Russian Metropolis - Kashtanov, Artem; Molotok, Ekaterina; Yavorovskiy, Andrey; Boyarkov, Alexander; Vasil’ev, Yuriy; Ali, Alsaegh; Dydykin, Sergey; Kytko, O. V.; Meylanova, Renata; Yulianna, Enina; Troitskiy, Vasiliy; Kapitonova, Marina; et al. (MDPI, 2022)
Working in intensive care units (ICUs) is stressful and potentially leads to various psychoemotional disorders. Today, this issue represents a serious concern to the healthcare sector and affects the quality of healthcare provided. This study aimed to assess and compare the psycho-emotional state in COVID-19 and non-COVID-19 hospitals’ ICU healthcare workers (HCWs). From January to July 2021, we conducted an anonymous cross-sectional web survey of ICU physicians and nurses (N = 1259) of various hospitals in a metropolis with a population of over 10 million people. The statistical distributions of non-COVID-19 ICU HCWs showed the following results: emotional exhaustion levels (low 14.6%, average 30.8%, and high 54.6%); depersonalization levels (low 11.6%, average 16.5%, and high 71.9%); and reduced personal accomplishment levels (low 23.5%, average 40.3%, and high 36.2%). The statistical distributions of COVID-19 ICU HCWs showed the following results: emotional exhaustion levels (low 16.5%, average 31.5%, and high 52%); depersonalization levels (low 7.4%, average 9.4%, and high 83.1%); and reduced personal accomplishment levels (low 25.4%, average 45.4%, and high 29.1%). This study found a strong correlation between emotional exhaustion, aggression, and depersonalization in non-COVID-19 ICU HCWs and also found a correlation between their age, aggression, emotional exhaustion, and occupational stress.